Frequency and Geographic Distribution of CARD9 Mutations in Patients With Severe Fungal Infections - Vaezi, Afsane; Fakhim, Hamed; Abtahian, Zahra; Khodavaisy, Sadegh; Geramishoar, Mohsen; Alizadeh, Ahad; Meis, Jacques F.; Badali, Hamid (Frontiers in Microbiology, 2018)
Autosomal recessive deficiency in the caspase recruitment domain containing protein 9 (CARD9) results in susceptibility to fungal infections. In the last decade, infections associated with CARD9 deficiency are more reported due to the advent of genome sequencing. The aim of this study was to evaluate the frequency, geographic distribution and nature of mutations in patients with CARD9 deficiency. We identified 60 patients with 24 mutations and different fungal infections. The presence of the homozygous (HMZ) p.Q295X (c.883C>T) and HMZ p.Q289X (c.865C>T) mutations were associated with an elevated risk of candidiasis (OR: 1.6; 95% CI: 1.18–2.15; p = 0.004) and dermatophytosis (OR: 1.85; 95% CI: 1.47–2.37; p <0.001), respectively. The geographical distribution differed, showing that the main mutations in African patients were different Asian patients; HMZ p.Q289X (c.865C>T) and HMZ p.Q295X (c.865C>T) accounted for 75% and 37.9% of the African and Asian cases, respectively. The spectrum of CARD9 mutations in Asian patients was higher than in African. Asia is the most populous continent in the world and may have a greater genetic burden resulting in more patients with severe fungal infections. The presence of a high diversity of mutations revealing 24 distinct variations among 60 patients emphasize that the unique genetic alteration in CARD9 gene may be associated with certain geographical areas.